Anti-corrosive properties of waterborne polyurethane/poly(o-toluidine)-ZnO coatings in NaCl solution. Issue 10 (19th May 2019) - Zhang, Jiawei; Li, Ying; Hu, Chuanbo; Huang, Wenlong; Su, Lin
Abstract: The aim of this research was to prepare waterborne polyurethane (WPU) coating blended with a series of poly(o-toluidine)-nano ZnO composites and study its anti-corrosion performance after its application over carbon steel. The synthesized composites were characterized by X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). The corrosion resistance of coatings with and without nano ZnO were studied in 3.5% NaCl solution at a temperature of 25 °C, by electro-chemical techniques such as potentiodynamic polarization measurements and electrochemical impedance spectroscopy (EIS). It was observed that the composite coating containing 7% poly(o-toluidine)-nano ZnO composite had higher corrosion resistance than poly(o-toluidine) and 14% poly(o-toluidine)-nano ZnO composite. The presence of appropriate amount of ZnO significantly improved the corrosion resistance, due to the formation of passive layer on steel surface and the synergistic effects of poly(o-toluidine) along with a suitable amount of nano-ZnO reduced the porosity of the coating surface.